1990
DOI: 10.2214/ajr.155.4.2119117
|View full text |Cite
|
Sign up to set email alerts
|

MR arthrography of the shoulder: comparison with conventional MR imaging.

Abstract: Twenty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
13

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(117 citation statements)
references
References 5 publications
3
100
1
13
Order By: Relevance
“…In our patients, MRA demonstrated the highest sensitivity at 94.4% among the groups in detecting Bankart lesions, which is similar to the results of studies (15)(16)(17), which advocate MRA as the gold standard for diagnosing anterior-inferior labral lesions. The advantages of MRA over other forms of imaging are the ability to detect subtle lesions of the intra-articular structures such as the labrum and ligaments (18).…”
Section: Discussionsupporting
confidence: 89%
“…In our patients, MRA demonstrated the highest sensitivity at 94.4% among the groups in detecting Bankart lesions, which is similar to the results of studies (15)(16)(17), which advocate MRA as the gold standard for diagnosing anterior-inferior labral lesions. The advantages of MRA over other forms of imaging are the ability to detect subtle lesions of the intra-articular structures such as the labrum and ligaments (18).…”
Section: Discussionsupporting
confidence: 89%
“…While MR arthrography is generally preferred over conventional unenhanced MRI for labral tears and has been shown to be more sensitive [7,8], previous studies evaluating MR arthrography, including T1W sequences, have reported a wide range of sensitivities. Palmer et al reported a sensitivity for labral tear of 92% [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Axial sequences were performed with TR/TE 434/11 ms, slice thickness 4 mm with an interslice gap of 0. 8 Review of the images was performed by three musculoskeletal radiologists with varying levels of experience (19,5, and 2 years). The radiologists were presented with either the paired axial and coronal GRE or the axial and coronal T1W sequences.…”
Section: Methodsmentioning
confidence: 99%
“…It can also provide clear discrimination between rotator cuff tears and small anatomical variations (5,6).…”
Section: Introductionmentioning
confidence: 99%